2015
DOI: 10.1515/dcse-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Awakening Pre-service Teachers to Children’s Social Exclusion in the Classroom

Abstract: Children’s social exclusion in the classroom is a threat to the sustainability of education. Teachers should be sensitised to this issue, which raises important implications for teacher education. This paper reports on an action research study in the context of pre-service teacher education aimed at enriching prospective early childhood educators’ perspectives on children’s social exclusion in the classroom and heightening their awareness of themselves as key figures in reducing it. A teacher capable of dealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In relation to the classroom environment, the classroom needs to become a community in which each person contributes and has value (Weber et al, 2010). Students should not experience social exclusion, as this will limit engagement and participation (Ged˛˚ne, 2015). Students should feel comfortable and open to discuss ideas, without feeling embarrassed, degraded, or humiliated (Weber et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the classroom environment, the classroom needs to become a community in which each person contributes and has value (Weber et al, 2010). Students should not experience social exclusion, as this will limit engagement and participation (Ged˛˚ne, 2015). Students should feel comfortable and open to discuss ideas, without feeling embarrassed, degraded, or humiliated (Weber et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, teaching style is the amalgamation of teachers' motivation, personality, attitudes, beliefs, and strategies. Teaching style might be affected by factors such as educational background, teaching and learning experience, cultural background, and personal interests (Felder & Henriques, 1995;Fischer et al, 2015;Gedzune, 2015;Heimlich & Norland, 1994;Kazlauskiene, Gaucaite, & Juodaityte, 2011;Keri, 2002;Nouraey & Karimnia, 2016;Tavakoli & Karimnia, 2017). These factors could be identified by observing and studying teachers' behavior.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Although student teaching is generally associated with positive emotions for pre-service teachers (Hascher, & Wepf, 2007), other emotions like ìanxiety, nervousness, and worryî are also prevalent (Hascher & Hagenauer, 2016, p. 22). Studies have found that student teaching prepares pre-service teachers for their role as a teacher and plays a significant role in teacher retention (Darling-Hammond, Newton, & Wei, 2010;Ged˛˚ne, 2015). Pre-service teachers need to feel connected and have a sense of self-efficacy for the responsibilities they face when teaching (Ryel, Bernsausen, & van Tassell, 2001).…”
Section: Pre-service Teachers and Self-efficacymentioning
confidence: 99%
“…To help pre-service teachers maintain their interest in the profession of teaching and use those skills to help all students they teach, it is paramount that they have a strong sense of self-efficacy (Ged˛˚ne, 2015). This is especially true for teachers who work in high-poverty, low-income schools.…”
Section: Introductionmentioning
confidence: 99%